The Merchant of Venice in Auschwitz: Taking Apart Shylock Using the SCM and BIAS Map - Knutson, Susan L. (Frontiers in Psychology, 2021)
In response to Frontiers’ 2020 Call for Papers on “Stereotypes and Intercultural Relations: Interdisciplinary Integration, New Approaches, and New Contexts,” my paper integrates the scientific study of stereotypes with a literary-theatrical exploration of stereotyping. The focus is on Tibor Egervari’s post-Auschwitz adaptation of Shakespeare’s anti-Semitic comedy The Merchant of Venice, with a brief look at his related work on Christopher Marlowe’s The Jew of Malta and his 1998 collaboration with conductor Georg Tintner on a touring production of composer Viktor Ullmann’s and librettist Peter Kien’s one-act opera, The Emperor of Atlantis, or Death’s Refusal, composed in the “model” concentration camp Terezín (Theresienstadt), in 1943-4. Egervari’s theatre art critically deconstructs what he calls “the Old Jew” stereotype in specific ways highly readable using the SCM and BIAS map. Theatre performance can sometimes embody the forceful dynamic traced by the BIAS map, from cognition to affect to behavior. Egervari’s original adapation. which sets of The Merchant of Venice in Auschwitz, reveals this dynamic clearly. My interdisciplinary study of Egervari’s theatrical-cultural work validates the SCM and BIAS map for literary studies and offers fresh interpretations of Shakespeare’s Merchant and Egervari’s anti-Nazi Shakespeare adaptation.